Zooplankton community characteristics of the different water types in Abu Qir Bay, Alexandria, Egypt - Howaida Y. Zakaria; Ahmed Radwan; Mohamed Said (Egyptian Journal of Aquatic Research, 2019)
Abu Qir Bay is a semicircular shallow basin lying at 35 km to the east of Alexandria City. It receives various types of continental discharges through three openings. Throughout the period 2012–2013, six surveys were carried out in the area to identify the water types based on salinity values and to investigate the zooplankton communities that characterize each water type.Based on the surface salinity distribution, three water types could be identified in the investigated area:Diluted water type (D) of salinity < 30.00 psu which mainly included the near shore stations that are affected by fresh water discharged from the three main resources. Zooplankton community in this water type was fairly abundant (24.6 × 103 ind.m−3) and less diversified (55 species) as the neritic community with low diversity inhabits brackish areas.Mixed water type (M) of salinity 30.00–38.50 psu was the most productive (29.3 × 103 ind.m−3) and diversified (85 species) water type. It attained a little number of fresh water forms (4 species).Mediterranean Sea water type (S) of salinity > 38.50 psu was mainly included the offshore stations encompass neritic and oceanic species with low densities. It attained the lowest zooplankton abundance (9.5 × 103 ind.m−3) and was fairly diversified (66 species totally marine forms). Keywords: Hydrography, Water types, Zooplankton, Mediterranean, Abu Qir Bay, Egypt